Egypt Daily Wheat Price Survey, 1998 - International Food Policy Research Institute (International Food Policy Research Institute, 2000)
The questionnaire was administered to randomly selected wholesale and retail traders in 18 governorates (Cairo and Alexandria; Damietta, Dakahlia, Sharkia, Ismailia, Qalubia, Kafr El-Sheikh, Gharbia, Menufia, and Beheira in Lower Egypt; Giza, Fayum, Beni Suef, and Minia in Middle Egypt; Assiut and Sohag in Upper Egypt; and Matruh of the Frontier governorates) from June 1997 through the end of May 1998. Data on the daily purchase and sale price for both wholesale and retail traders were collected for domestic wheat grain, 82% extraction (baladi) flour, domestic 72% extraction (fino) flour, and imported 72% extraction (fino) flour.